Assessing self-responsibility in employability competencies development among Australian engineering students: introductory report - Lazarus, D.; Ferris, Timothy L. J. (Industrial Engineering and Operations Management Society, 2016)
Self-responsibility study initially outlined the importance of ‘self-directed Adult learning’ either as the method or the outcome of education. Attention was given to the different interest of individual’s in accepting responsibility for their professional development. In this regard, several sources reveal the need for learners to take their own responsibility for developing employability competencies development. However, the concern must be expressed at the incompleteness of research into the personal responsibility for competency development.